PERLINDUNGAN HUKUM BAGI PEJABAT PEMERINTAHAN DARI ANCAMAN PIDANA DALAM PENGGUNAAN DISKRESI - Ghozali, Moudy Raul; Hadi, Syofyan (Mimbar Keadilan, 2021)
The purpose of the study was to determine the form of legal protection for officials from criminal threats in using discretion. Using pure legal research. There are two forms of legal protection in the use of discretionary authority, namely preventive legal protection and repressive legal protection. The first preventive legal protection is contained in Article 67 of Law no. 5-2009 or also known as the principle of praesumptio iustae causa, namely decisions issued by government officials are always considered valid until there is an annulment. The second preventive legal protection is that the policy principle cannot be criminalized. Government policies cannot be criminalized if there are no elements of harming state finances and benefiting themselves or other parties. As well as the implementation of these policies for public services. While the repressive legal protection is contained in Article 21 paragraph (1) of Law no. 30-2014 and Perma No. 4-2015, which determines that the Administrative Court has the authority to receive, examine, and decide whether or not there is an element of abuse of authority committed by government officials.Keywords: discretion; officials; legal protectionAbstrakTujuan penelitian untuk mengetahui bentuk perlindungan hukum bagi pejabat dari ancaman pidana dalam menggunakan diskresi. Menggunakan peneltiian hukum murni. Terdapat dua bentuk perlindungan hukum dalam penggunaan wewenang diskresi, yakni perlindungan hukum preventif dan perlindungan hukum represif. Perlindungan hukum preventif yang pertama tertuang dalam Pasal 67 UU No. 5-2009atau dikenal juga dengan asas praesumptio iustae causa yakni keputusan yang dikeluarkan oleh pejabat pemerintahan selalu dianggap absah hingga ada pembatalannya. Perlindungan hukum preventif yang kedua adalah prinsip kebijakan tidak dapat di pidana. Kebijakan pemerintah tidak dapat di pidana apabila tidak ada unsur merugikan keuangan negara dan menguntungkan diri sendiri ataupun pihak lain. Serta pelaksanaan kebijakan tersebut untuk pelayanan publik. Sedangkan perlindungan hukum represif tertuang pada Pasal 21 ayat (1) UU No. 30-2014 dan Perma No. 4-2015, yang menentukan bahwa PTUN berwenang untuk menerima, memeriksa, dan memutus ada atau tidak unsur penyalahgunaan wewenang yang dilakukan oleh pejabat pemerintahan.